2014
DOI: 10.48550/arxiv.1412.1634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monotonicity of ratios of q-Kummer confluent hypergeometric and q-hypergeometric functions and associated Turán types inequalities

Khaled Mehrez,
Sergei M. Sitnik

Abstract: In this paper we prove monotonicity of some ratios of q-Kummer confluent hypergeometric and q-hypergeometric functions. The results are also closely connected with Turán type inequalities. In order to obtain main results we apply methods developed for the case of classical Kummer and Gauss hypergeometric functions in [1]-[2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Recently the authors also proved generalizations of above monotonicity properties and Turán type inequalities for the case of q-hypergeometric functions [26]- [27].…”
Section: Proofmentioning
confidence: 99%
“…Recently the authors also proved generalizations of above monotonicity properties and Turán type inequalities for the case of q-hypergeometric functions [26]- [27].…”
Section: Proofmentioning
confidence: 99%
“…Motivated by these applications, the Turán type inequalities have recently come under the spotlight once again and it has been shown that, for example, the classical Gauss and Kummer hypergeometric functions, as well the generalized hypergeometric functions, satisfy naturally some Turán type inequalities [8,9,10]. For deep study about this subject we refer to [2,3,4,11].…”
Section: Introductionmentioning
confidence: 99%